2001
DOI: 10.1071/sr00036
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of soil with fluoride by long-term application of superphosphates to pastures and risk to grazing animals

Abstract: Fluoride (F) is an impurity in phosphatic fertilisers and significant amounts of F will be added to soils with long-term application of phosphatic fertiliser to soil. There is a risk that F concentrations in soil may increase to levels toxic to plants or grazing animals. If F added to soil remains in the upper soil profile, due to high reactivity with soil, grazing animals could increase their intake of F through inadvertent ingestion of F-enriched soil. This study determined the distribution of F in the soil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…In soil solutions extracted by 0.01 M CaCl 2 from highly acidic (pH in 0.01 M CaCl 2 , 4.7-4.8) Australian pastoral topsoils (0-100 mm depth), 95%-98% of the F was estimated to be complexed with Al (McLaughlin et al 2001). However, in the subsurface soils (200-300 mm depth) that had pH (in 0.01 M CaCl 2 ), >5.2, F − was the dominant form of F in soil solutions.…”
Section: Cadmium and Fluorine Forms In Pastoral Soilsmentioning
confidence: 99%
See 1 more Smart Citation
“…In soil solutions extracted by 0.01 M CaCl 2 from highly acidic (pH in 0.01 M CaCl 2 , 4.7-4.8) Australian pastoral topsoils (0-100 mm depth), 95%-98% of the F was estimated to be complexed with Al (McLaughlin et al 2001). However, in the subsurface soils (200-300 mm depth) that had pH (in 0.01 M CaCl 2 ), >5.2, F − was the dominant form of F in soil solutions.…”
Section: Cadmium and Fluorine Forms In Pastoral Soilsmentioning
confidence: 99%
“…In highly acidic soils with large inputs of F, however, the F concentration of pasture may be high. For example, in an Australian pasture soil of pH (CaCl2) of 4.6, it was reported that the mean pasture herbage F concentration (22 mg F/kg DM) in P-fertilized plots (annually topdressed with 125 kg SSP/ha for 36 yr) was signifi cantly higher than that (11 mg F/kg DM) in the unfertilized plots (McLaughlin et al 2001). Similarly, of 12 soils around aluminium smelters in Norway, in 11 soils having pH 4.1-5.8 and a water soluble F of 1-6 mg/kg, the F concentration in ryegrass shoots was 3-9 mg/kg, but in a highly F-contaminated soil having a pH of 4.9 and water-soluble F concentration of 33 mg/kg the F concentration in ryegrass shoots reached levels of 15-18 mg/kg (Arnesen 1997).…”
Section: Capeweed (Arctotheca Calendula L) Is a Common Component Of mentioning
confidence: 99%
“…Fluorine is usually present in soils as the fluoride ion (F À ), usually retained on soil mineral surfaces by ligand exchange reactions, or incorporated into soil minerals, for example fluorite. Fluorine in soil solution is either present as the free F À ion or as complexes with Al or H [117,118]. The free F À ion is highly reactive with soil components and is retained strongly by soils [119], thus fertilizer-derived F accumulates at the soil surface [42,118].…”
Section: Fluorinementioning
confidence: 99%
“…Fluorine in soil solution is either present as the free F À ion or as complexes with Al or H [117,118]. The free F À ion is highly reactive with soil components and is retained strongly by soils [119], thus fertilizer-derived F accumulates at the soil surface [42,118]. The strong retention of F by soil also results in low soil-plant transfer coefficients [120], unless F is complexed by H [121] or Al [122].…”
Section: Fluorinementioning
confidence: 99%
“…Fluoride is also an impurity in phosphate fertilizers. Long-term application of phosphate fertilizer can lead to the risk that F concentrations in a soil may increase to phytotoxic levels (McLaughlin et al 2001). Fluoride can be adsorbed strongly by variable charge soils (Bower & Hatcher 1967;Shao & Chen 1986;Liu 1988;Yu 1997) and this process decreases the activity and availability of F ) to plants.…”
Section: Introductionmentioning
confidence: 98%